MEMAHAMI FUNGSI DAN JENIS KATALOG DALAM PERPUSTAKAAN: PANDUAN UNTUK PEMUSTAKA DAN MENGELOLA PERPUSTAKAAN - Ariska, Sefin; Nurhidayah, Srinita; Kurnia Vlora, Rani (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2025)
A library is a place to store various types of library materials, such as books, journals, magazines, and so on. Catalogs consist of several types, such as card catalogs, online catalogs, and published catalogs. Each type of catalog has its own advantages and disadvantages. Therefore, readers need to understand these types of catalogs in order to make good use of them. Apart from that, library managers also need to understand the functions and types of catalogs in order to manage the library well. In processing library materials, libraries need to follow established rules so that library materials can be stored and recovered quickly, precisely and accurately when needed by the user. Cataloging is one of the important processes for processing library materials, namely recognizing the physical collection and recognizing the contents of the collection. In processing library materials, libraries also need to pay attention to the processing of e-resource type library materials and their processing. In an effort to provide excellent service to users, all types of library materials need to be processed properly in accordance with established rules so that they stored & recovered quickly, precisely & accurately needed by users.